2012
DOI: 10.1021/jm301414f
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of T7 and T12 Residues on the Biological Properties of Thrombin-Binding Aptamer: Enhancement of Anticoagulant Activity by a Single Nucleobase Modification

Abstract: An acyclic pyrimidine analogue, containing a five-member cycle fused on the pyrimidine ring, was synthesized and introduced at position 7 or 12 of the 15-mer oligodeoxynucleotide GGTTGGTGTGGTTGG, known as thrombin-binding aptamer (TBA). Characterization by 1H NMR and CD spectroscopies of the resulting aptamers, TBA-T7b and TBA-T12b, showed their ability to fold into the typical antiparallel chairlike G-quadruplex structure formed by TBA. The apparent CD melting temperatures indicated that the introduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 52 publications
7
47
0
Order By: Relevance
“…In contrast, the TGT loop showed higher conformational flexibility, especially concerning the T7 residue, which is reported to interact with thrombin in some X-ray complexes. 11,12 Previous structure-activity relationship (SAR) studies on TBA analogues containing an acyclic nucleotide, performed by us 16,17 and others, 18,19 confirmed that some loop residues, specifically T4, T13, G8, and T9, are crucial to preserve the G-quadruplex folding typology, whereas the others, T3, T12, and T7, are uniquely involved in thrombin inhibition. Indeed, ONs modified at T3, T12, and T7 showed significantly different biological behaviours with respect to TBA, not related to the stability of their G-quadruplex structure.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, the TGT loop showed higher conformational flexibility, especially concerning the T7 residue, which is reported to interact with thrombin in some X-ray complexes. 11,12 Previous structure-activity relationship (SAR) studies on TBA analogues containing an acyclic nucleotide, performed by us 16,17 and others, 18,19 confirmed that some loop residues, specifically T4, T13, G8, and T9, are crucial to preserve the G-quadruplex folding typology, whereas the others, T3, T12, and T7, are uniquely involved in thrombin inhibition. Indeed, ONs modified at T3, T12, and T7 showed significantly different biological behaviours with respect to TBA, not related to the stability of their G-quadruplex structure.…”
Section: Introductionmentioning
confidence: 89%
“…[11,12] Further factorst hat contribute to the wide polymorphism of G-quadruplexes are the length and the base composition of the loops (when present), as well as the nature of the cationsu sed to stabilize the quadrupleh elix structure. [13][14][15] The biological implications of Gquadruplexes in cellular processes [16][17][18] and their use as promising drugs [19][20][21][22] or in drugs delivery [23] and diagnostics [23][24][25] are well known. In addition, G-quadruplexes possess greater conductivityt han DNA duplexes, thus suggesting their use for the obtainment of electronic nano-biomaterials and nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the systematic introduction of a single UNA‐U nucleotide at position T3, T7 or T12 increased the thermodynamic stability of TBA, and the presence of unlocked nucleic acid (UNA)‐U at position 7 showed high potency with regard to inhibition of fibrin clot formation . Borbone and colleagues reported similar results by modifying TBA at position T7 with an acyclic pyrimidine analogue . In two recent studies, Virgilio et al.…”
Section: Introductionmentioning
confidence: 92%
“…With regard to the structure and interaction with thrombin, a number of investigations have shown that the loop regions of TBA are crucial for thrombin interaction and G‐quadruplex formation . Previous structure–activity relationship (SAR) studies revealed that loop residues T4, T9, T13 and G8 are critical to preserve the G‐quadruplex structure, and that T3, T7 and T12 are more flexible moieties that are particularly involved in thrombin inhibition . Krauss et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation